2014
DOI: 10.1007/s00192-014-2423-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pelvic muscle architecture between humans and commonly used laboratory species

Abstract: Introduction and hypothesis Pelvic floor muscles (PFM) are deleteriously affected by vaginal birth, which contributes to the development of pelvic floor disorders. To mechanistically link these events, experiments using animal models are required, as access to human PFM tissue is challenging. In choosing an animal model, a comparative study of PFM design is necessary, since gross anatomy alone is insufficient to guide the selection. Methods Human PFM architecture was measured using micromechanical dissection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
53
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 30 publications
0
53
0
Order By: Relevance
“…PFM architecture of 3-month-old Sprague-Dawley female virgin rats, which served as a control group, was previously reported. 26 Collagen content of the PFMs of virgin controls was determined using previously preserved tissue. Ten intermediate (4 weeks) and 10 late (12 weeks) postpartum animals were studied to determine whether PFMs returned to prepregnancy state.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…PFM architecture of 3-month-old Sprague-Dawley female virgin rats, which served as a control group, was previously reported. 26 Collagen content of the PFMs of virgin controls was determined using previously preserved tissue. Ten intermediate (4 weeks) and 10 late (12 weeks) postpartum animals were studied to determine whether PFMs returned to prepregnancy state.…”
Section: Methodsmentioning
confidence: 99%
“…Individual pelvic muscles were identified by tracking each muscle from its origin to insertion, weighed and divided into 3 regions, as previously described. 26 Tibialis anterior muscles were identified, harvested, and processed in parallel. The following architectural parameters were quantified: fiber length (L f ), a predictor of contractile velocity and muscle excursion; physiologic cross-sectional area (PCSA), proportional to the maximum force a muscle can generate isometrically; and sarcomere length (L s ), the “molecular machine” that determines a muscle’s active force (ie, the force a muscle produces when stimulated).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparison of PFM structural parameters between human and rat demonstrated architectural similarity, suggesting that they have comparable functional design. 20 The rat model also has proven valuable in many studies of pregnancy-related changes in other pelvic structures. 17,21,22 Furthermore, we recently reported that adaptations during pregnancy occur in the myofibers of rat PFMs, which increase their length by adding sarcomeres in series.…”
mentioning
confidence: 99%